Epilepsy-related long-term amnesia: Anatomical perspectives - Butler, C; Kapur, N; Zeman, A; Weller, R; Connelly, A (2012)
There are few clues as to the neural basis of selective long-term amnesia. We report group and single-case data to shed light on this issue. In a group study of patients with transient epileptic amnesia, there were no significant correlations between volumetric measures of the hippocampus and indices of accelerated long-term forgetting or longer-term autobiographical memory loss. Post-mortem investigations in a patient with temporal lobe epilepsy who showed accelerated long-term forgetting, together with a degree of autobiographical memory loss, yielded evidence of neuronal loss and gliosis in regions of both the right and the left hippocampus. Neuronal loss and gliosis were more evident in anterior than posterior hippocampus. These results indicate that the unusual forms of long-term forgetting seen in some patients with temporal lobe epilepsy have no gross anatomical correlate. The findings leave open the possiblities that subtle structural damage or subtle functional disturbance, perhaps in the form of subclinical epileptiform activity, underly epilepsy-related long-term amnesia. © 2012 Elsevier Ltd.